Towards “Autopoetics” (retour sur e-Rea 5.2 2007) - Hélène AJI (E-REA)
This short essay picks up where the 2007 issue of e-Rea on “Poetry and Autobiography” had left off. It recontextualizes the debate over autobiography and literary genre, especially as it took place in the wake of Philippe Lejeune’s Pacte autobiographique. The outright dismissal of poetry as the locus for autobiography is thus revisited, and the formal experiments allowed by the poetic form to question the narrative linearity and coherency of the prose autobiographical account are historicized. The idea of an “autopoetics” then emerges from the possibility that the poetic could be the mode whose discontinuities align with the representation of today’s disorganized and disorganizing identities.